Sources of Business Cycles in Energy Producing Economies - The case of Norway and United Kingdom - Hilde Christiane Bjørnland (Statistics Norway, Research Department, 1996)
This paper analyses the sources of business cycles in economies that have an important energy producing sector. Especially, I investigate the effects of oil and gas extractions (energy booms) on the manufacturing sector, and analyse whether there is any evidence of a "Dutch disease", that is whether energy booms have had adverse effects on the manufacturing base. In additions to energy booms, I identify three other types of disturbances in the economy; aggregate demand, supply and oil price shocks. The different structural disturbances are identified by imposing long-run and short-run (zero) restrictions on a vector autoregressive model. The analysis is applied to Norway and United Kingdom, which both discovered huge oil resources in the North Sea in the 1970s. There is no evidence of a Dutch disease in Norway, and manufacturing output has actually benefited from both energy discoveries and higher oil prices. In UK on the other hand, manufacturing output has declined in response to energy booms, although the effect is small compared to the effects of the other shocks that are present at the time.
Keywords: C22; C32; E32; L60; Q43; 330; Dutch disease; dynamic restrictions; structural vector autoregression.